GAMBARAN REMAJA PUTRI USIA 14 â 16 TAHUN TENTANGCARA MENANGANI NYERI HAID DI SMP TAMAN SISWAKOTA MOJOKERTO - Ratnaningsih, Tri; Purwa Seven, Nilam (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Reproductive health is an important issue for teenagers. The earliest changes in young women was to start having periods which can lead to menstrual pain that can be debilitated and can indirectly impact on productivity and quality of life of young women. The purpose of the research to find a picture of young women aged 14-16 years about how to deal with menstrual pain in the Junior Student Park Mojokerto. Design research use descriptive research. The entire population of young women who has experienced a primary dysmenorrhoea and menstrual age of 14-16 years . They were 55 respondents to obtain a sample of 31 respondents were taken by purposive sampling. The data were taken used a questionnaire with Likert scale, then interpreted in the form of a frequency distribution table for the data public and to specific data. This research implementation in SMP Taman Siswa Mojokerto city in Okt 2014. This research used presentil data with cross tab data analisys. The results show that young women deal with painful menstruation are not exactly as many as 19 young women (61.3%), most of the respondents aged 16 years old with 14 girls (45.16%). Young women deal with painful menstruation is not exactly as many as 19 young women (61.3%). This is due to the lack of information they receive, so teens need to seek information from the mass media or ask the teacher / parent, and can attend seminars on dysmenorrhoea than positive information, if someone is getting a lot of knowledge to get the information more widely and more level of knowledge in dealing with menstrual pain appropriately.Keywords: dysmenorrhoea, how to deal with painful menstruation, young women